Facilitators and Barriers to Implementation of a Childhood Tuberculosis Control Program in Bangladesh: A Mixed-Methods Study from BRAC Urban DOTS Centres in Dhaka - Sandesh Pantha; Ma. Jennylyn Aguinaldo; S. M. Hasan-; Sayantan Chowdhury; Ugyen Dendup; Rajat Das Gupta; Ipsita Sutradhar; Rahamatul Bari; Malabika Sarker (MDPI AG, 2022)
The case detection rate of childhood tuberculosis in Bangladesh is 4%, far below the World Health Organization predicted rate of 10-15% for a country with a high burden of tuberculosis. A concurrent triangulation mixed-methods study was carried out in eight urban DOTS (Directly Observed Treatment, Short-course) centres to investigate the factors contributing to the diagnosis and treatment of childhood tuberculosis. Front-line health care workers (Shasthya Shebika) (n = 111) were surveyed to understand knowledge, attitude, and practice (KAP) of the diagnosis and treatment of childhood tuberculosis. In-depth interviews were conducted with field workers (n = 32) and mothers of TB cases (n = 4). Stakeholders involved in implementing the tuberculosis program (n = 9) participated in the key informant interviews. Knowledge of Shasthya Shebika was associated with the components addressed during refresher training (p = 0.02). Government stewardship, presence of specific guidelines, knowledge and capacity building of front-line health workers were identified as the key facilitators. Frequent turnover of key managerial positions in the government, stigma, delays in seeking care, lack of diagnostic facilities, and poor engagement of private practitioners were identified as major constraints. It was identified that the government should focus on improving diagnostic capacities, conduct research on childhood tuberculosis, and produce awareness materials.